The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/flan.12333
|View full text |Cite
|
Sign up to set email alerts
|

Language in a global world: A case study of foreign languages in U.S. K–8 education

Abstract: Over the past decade, there have been numerous calls to update U.S. education to reflect an increasingly global world (Hull & Hellmich, 2018). Foreign languages (FLs) are often perceived as central to these efforts (American Academy of Arts & Sciences, 2017). Despite this centrality, less is known about how FLs are understood in U.S. K–12 education today, particularly at the individual and school levels. Using an ecological theoretical frame and a case study research design, this article focused on one K–8 imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Interview data produced similar findings in a recent study on a private immersion school with French and Spanish as the partner languages (Hellmich, ). In that study, a heritage speaker of Spanish expressed that learning Spanish was important to her because Spanish skills will be helpful for future careers, and both heritage speakers and nonheritage speakers in the study mentioned that learning the partner language is useful when they travel to other countries.…”
Section: Literature Reviewsupporting
confidence: 76%
See 1 more Smart Citation
“…Interview data produced similar findings in a recent study on a private immersion school with French and Spanish as the partner languages (Hellmich, ). In that study, a heritage speaker of Spanish expressed that learning Spanish was important to her because Spanish skills will be helpful for future careers, and both heritage speakers and nonheritage speakers in the study mentioned that learning the partner language is useful when they travel to other countries.…”
Section: Literature Reviewsupporting
confidence: 76%
“…The survey and focus group interview methods were used to assess students’ attitudes, as in previous studies (Bearse & de Jong, ; Hellmich, ; Lindholm‐Leary, ). Eight background questions adapted from Lindholm‐Leary () were used to elicit the demographic information reported above.…”
Section: Methodsmentioning
confidence: 99%
“…Tedick and Wesely (2015) assert that there is little peer‐reviewed, empirical evidence of the components of effective FLIP administration. Studies have shown a need for educational leaders to better understand FLIPs characteristics and design (Cammarata & Tedick, 2012; Hellmich, 2018; Olson Beal et al, 2012). This study addressed these research gaps by examining school administrators’ understanding and planning of the FLIP's components within the specific context of French Immersion.…”
Section: Literature Reviewmentioning
confidence: 99%